Synthesis of Biologically Active and Novel Antifungal Agents Like Substituted Hetero Aryl amines of Dihydro Imidazo[1,2-a]pyridine Derivatives - Venkat Rao, S.; Komali, D.; K. Ameer, Sk.; Raju, S.D.V.V.S.S.; Naveen Reddy, K. (Asian Journal of Chemistry, 2012)
Some substituted hetero aryl amines of dihydro imidazo[1,2-a]pyridine-3yl-methyl derivatives were synthesized and the final compounds elucidated by FTIR, 1H NMR, MASS and micro analysis and were evaluated for antifungal activity by Candida albcans. The preliminary results showed that all of the tested compounds were protective against Candida albcans at 50-200 mcg/mL concentrations levels.